Convergent Synthesis of the Pentasaccharide Repeating Unit of the O-Antigen of Escherichia coli O36 - Mandal, Pintu Kumar (Synthesis, 2015)
An efficient synthesis of the pentasaccharide repeating unit of the O-antigen of Escherichia coli O36 is reported. A stereoselective [2 + 3] block glycosylation method has been exploited to obtain the target pentasaccharide derivative using thioglycoside, trichloroacetimidate, and halide-exchange glycosylation procedures. The 2-azidoethyl group has been used as the anomeric protecting group to make the glycone moiety with a readily available linker for its conjugation to a protein without destroying the cyclic structure at the reducing end. Yields were high in all the intermediate steps.
Keywords: Escherichia coli; pentasaccharide; glycosylation; lipopolysaccharide; O-antigen